DOP54 Time to effect of biologics and small molecules for patients with moderately to severely active luminal Crohn's disease – a systematic review and network meta-analysis. (30th January 2023) - Attauabi, M; Steenholdt, C; Burisch, J; Gubatan, J; Nielsen, O H; Seidelin, J B
Abstract: Background: Patients with moderately to severely active luminal Crohn's disease (CD) have a high inflammatory burden, which can result in irreversible complications and therefore require urgent treatment. However, the speed of onset of efficacy of advanced agents is unclear. Therefore, we aimed to assess the onset of efficacy of biological therapies and small molecules for this adult patient population. Methods: For this systematic review and network meta-analysis, we searched MEDLINE, Embase, and Cochrane Central Register of Controlled Trials between inception and Sep 10, 2022. We included original data from randomized clinical trials and open-label interventional studies. The co-primary outcomes were clinical response, defined as i) ≥70-point or ii) ≥100-point reduction in Crohn's Disease Activity Index (CDAI-70 and CDAI-100) from baseline, and clinical remission, defined as CDAI ≤ 150 at week 2. Network meta-analysis was conducted under the Bayesian framework. This study is registered with PROSPERO: CRD42022368509. Results: Of 10, 129 and 19, 281 studies from databases and congress proceedings, 61 studies comprising 17, 436 patients were eligible for this study. Adalimumab 160/80 mg, adalimumab 80/40 mg, and certolizumab 400 mg were evaluated for the induction of a CDAI-70 and CDAI-100 response at week 2 and were all superior to placebo. Further, data on upadacitinib 45 mg once daily, vedolizumab 300 mg, and ustekinumab 6 mg/kg were reported for CDAI-100 response at week 2, with the former ranking highest and the latter ranking lowest. Of note, vedolizumab 300 mg did not achieve statistical superiority compared to placebo. However, no statistically significant difference between the agents was found (Figure 1). Further, the biosimilar BI 69550 160/80 mg and adalimumab 160/80 mg ranked highest and were superior to filgotinib 200 mg for achieving CDAI remission at week 2 (Figure 2). The latter ranked lowest and was, along with vedolizumab 300 mg, not superior to placebo for achieving CDAI remission at week 2 (Figure 2). Findings were consistent in the sensitivity analysis for bio-naïve and bio-exposed patients. However, in the sensitivity analysis of efficacy at week 4 in bio-exposed patients, ustekinumab 6 mg/kg ranked highest for both CDAI-70 and CDAI-100 responses (Figure 3). Sensitivity analysis on modes of action did not yield statistically significant differences. Conclusion: In this network meta-analysis, we found adalimumab 160/80 mg and upadacitinib 45 mg to be the preferred agents for rapid induction of clinical response and clinical remission at week 2, while vedolizumab 300 mg, filgotinib 200 mg, and ustekinumab 6 mg/kg might have a relatively slower onset of effect in this patient population.